Single-Cell RNA-seq Reveals Angiotensin-Converting Enzyme 2 and Transmembrane Serine Protease 2 Expression in TROP2+ Liver Progenitor Cells: Implications in Coronavirus Disease 2019-Associated Liver Dysfunction - Seow, Justine Jia Wen; Pai, Rhea; Mishra, Archita; Shepherdson, Edwin; Lim, Tony Kiat Hon; Goh, Brian K. P.; Chan, Jerry K. Y.; Chow, Pierce K. H.; Ginhoux, Florent; DasGupta, Ramanuj; Sharma, Ankur (Frontiers in Medicine, 2021)
The recent pandemic of coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 was first reported in China (December 2019) and now prevalent across the globe. Entry of SARS-CoV-2 into mammalian cells require the binding of viral Spike (S) proteins to the ACE2 (angiotensin converting enzyme 2) receptor. Once entered the S protein is primed by a specialised serine protease, TMPRSS2 (Transmembrane Serine Protease 2) in the host cell. Importantly, beside respiratory symptoms, consistent with other common respiratory virus infection when patients become viraemic, a significant number of COVID-19 patients also develop liver comorbidities. We explored if specific target cell-type in the mammalian liver, could be implicated in disease pathophysiology other than the general deleterious response to cytokine storms. Here we employed single-cell RNA-seq (scRNA-seq) to survey the human liver and identified potentially implicated liver cell-type for viral ingress. We analysed ~300,000 single cells across five different (i.e. human fetal, healthy, cirrhotic, tumor and adjacent normal) liver tissues types. We report the co-expression of ACE2 and TMPRSS2 in a TROP2+ liver progenitor population. Importantly, we detected enrichment of this cell population in cirrhotic liver when compared to tumor tissue. These results indicated that in COVID-19 associated liver dysfunction and cell death, viral infection of TROP2+ progenitors in liver may significantly impaired the liver regeneration in patients with liver cirrhosis.